Mediatized Image Politics of an ICE Raid, Staged in a Midwestern Idyll - Jennifer F. Reynolds (Semiotic Review, 2023)
This article shows how constitutive news media displays of contrasting chronotopes (i.e., peopled time-space imageries), both major and small, engendered an interpellative politics to channel white virtue while also flipping the script of U.S. imaginaries constructing who belongs within small-town Midwestern America. It examines the mediatized image politics of internal immigration border enforcement back when the Bush Administration was scaling up militarized tactics and experimenting with expedited legal procedures that sought to erase the lines dividing immigration from criminal law. It weighs in on cross-disciplinary debates of visual cultural practices depicting migrant (in)visibility in so-called new immigrant destinations, located in rural places across the Midwestern United States. The analysis unpacks heterogeneous cooccurring indexical signs in a mainstream AP broadcast news feature and a subsequent documentary film that compose image-texts of a raid on a purported idyllic town. Both mediatized image-texts of continuing coverage were oriented to multiple publics and made an example of a large-scale Immigration and Customs Enforcement (ICE) raid on an industrial meat processing and packing facility in 2008. News agents along with the active participation of migrant laborers and members of a humanitarian coalition co-operatively fashioned these productions to achieve different and multiple ends.